DIGITALISASI PEMBANGUNAN PENDIDIKAN: STRATEGI TERINTEGRASI UNTUK MEWUJUDKAN TRANSFORMASI PENDIDIKAN DI ERA DIGITAL - Thahir, Irmawati; Rostini, Rostini; Parawansa, Parawansa (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
This study examines the implementation of an integrated community service program for digital education development to address the digital divide in Tamasaju Village, Galesong Utara District, Takalar Regency. Driven by the challenges of unequal digital literacy and educational infrastructure, the program aims to realize a holistic transformation through a qualitative approach using a descriptive analytical case study method. The community service was divided into three main phases: preparation and socialization, implementation and training, and monitoring and evaluation. Research subjects included 20 teachers, 450 students, and key informants from two target schools, with data collected through observation, interviews, and pre-post surveys. The results show that the program successfully improved teachers' digital literacy, integrated learning technology, and encouraged the creation of digital content. This success confirms that effective and sustainable educational digitalization depends on an integrated strategy involving human resource development, infrastructure, and curriculum. As a recommendation, the program's sustainability is suggested through strengthening partnerships and establishing a community-level technology management team, making this model a replicable case study for other regions in Indonesia.